Confirmatory Factor Analysis on Educational Employees Engagement (Structural Equation Modeling Analysis) - Fatwa Tentama; Subardjo Subardjo (Journal of Educational, Health and Community Psychology, 2022)
An organization needs employees with high employee engagement with their organization to achieve goals. This study aims to determine employee engagement of the educational employees of X University. The population of the research was all educational employees at X University with the total sample of 202 subjects. The sampling technique used was simple random sampling method. The measurement instrument is the employment engagement scale. The analysis done by means of Structural Equation Modeling (SEM) with Second Order Confirmatory Factor Analysis (2nd Order CFA). The results of the research that the educational employees of X University show high employee engagement. The most dominant aspect, which reflect employee engagement is management support and the lowest aspect, which reflects employee engagement is sense of belonging.Keywords: confirmatory factor analysis, employee engagement, structural equation modeling